An Applicator Delivery System for Fixed-Combination Calcipotriene Plus Betamethasone Dipropionate Topical Suspension (Gel): Innovating Psoriasis Vulgaris Treatment Through Patient Collaboration. Issue 4 (December 2015) - Rasmussen, Gritt; Bech, Lene; Nielsen, Torben
Abstract Treatment non-adherence is a complex problem encountered in all therapy areas, particularly in chronic diseases such as psoriasis vulgaris. To address adherence issues, focus is turning towards developing interventions tailored to individual patient needs. Topical therapies remain the mainstay of psoriasis treatment; however, these are associated with additional challenges where preparations may be perceived as messy, inconvenient and time-consuming. Once-daily fixed-combination calcipotriene 0.005% (Cal) and betamethasone dipropionate 0.064% (BD) topical suspension is a convenient and effective first-line topical psoriasis therapy. To improve the patient experience with this treatment, we undertook a program—in collaboration with patients and healthcare professionals—to develop a topical treatment delivery system that further caters to the unmet needs of psoriasis patients. The finalized Applicator comprises: an easy to operate pump-action lever providing consistently accurate dose delivery (0.05 g of Cal/BD topical suspension/pump); a single-tip nozzle allowing for targeted, precise application to body and scalp psoriasis plaques; two spreading surfaces designed to disperse treatment evenly across both large and small affected skin areas; and a protective cover. Patients listed the following as key Applicator attributes: ease of use, 'less messy' treatment, precise application, consistent accurate dosing, 'no touch' treatment, reduction of wasted treatment and extended length of reach for awkward areas. Although these attributes were well received by most patients and healthcare professionals, some patients did not perceive them all as improvements over their current treatment; this highlights the need to tailor treatment for each individual patient's requirements. For patients who prefer using the Applicator, it has the potential to provide greater control over their daily psoriasis management by providing a simple, convenient treatment option, with minimal impact on their lives. The Applicator may represent a more acceptable treatment delivery system for some patients with psoriasis vulgaris and may, therefore, promote long-term treatment adherence. Funding : LEO Pharma